Probiotics Supplementation and Performance of Broiler Rabbits - Sharma, K. Geetanjali; Vidyarthi, V. K.; Zuyie, R. (Indian Journal of Animal Nutrition, 2018)
The experiment was conducted to investigate the effect of different levels of probiotics on performance of Soviet Chinchilla rabbits. For this, 15 growing rabbits (7 weeks old) were randomly distributed into 3 treatment groups consisting of 5 animals in each group. The rabbits in control group (T1) were fed with broiler finisher ration. The rabbits of the other two groups were also provided the same broiler finisher diet as in T1 group along with probiotics at a level of 2.5 g (T2) and 5.0 g (T3) per kg feed. The average live weight of the rabbit was similar (mean 2.16 kg) while gain in live weight was higher (P